Precipitation Behavior and Magnetic Properties of Cu-Fe-Co Alloys Containing Nanogranular Ferromagnetic-Element Particles. (20th October 2015) - Wada, N.; Kuwada, K.; Kim, J. S.; Takeguchi, M.; Takeda, M.
Abstract : This work investigates the evolution of microstructures and magnetic properties during isothermal annealing of Cu-Fe-Co alloys, using electron microscopy and superconducting quantum interference device (SQUID) magnetometry. Small coherent granular precipitates composed of iron and cobalt formed in the copper matrix in the early stage of precipitation. As annealing proceeded, the precipitates lost coherency to the matrix after reaching a size of 15–20 nm and twin-like structures were consecutively introduced in the particles. The SQUID measurements revealed that the magnetic properties of the specimens correlated with the microstructural evolution. The coercive force initially increased with annealing time but decreased after reaching a peak. Lorentz Microscopy suggested that the initial large increase of magnetization was invoked by a structural transition from fcc to B2 in the precipitates.